Attributions and difficulties presented by the nurse operation room surgical center (Research, Society and Development, 2022)
The Surgical Center is a structure of high complexity, which has restricted access, with its own rules and routines, thus constituting a unique hospital unit. In view of this, the following research aims to address the main attributions and difficulties presented by the operatiom room nurse in the Surgical Center. The following research corresponds to a descriptive study, with a qualitative methodological approach, using as technique the Integrative Literature Review in conjunction with the PICO strategy to formulate the guiding question. The research was conducted between the months of September and October 2021 in the databases available and indexed in the Virtual Health Library, namely: MEDLINE; LILACS, and BDENF, through the combination of three Health Descriptors, crossed with the Boolean operator "AND": Surgical Centers AND, Role of the Nursing Professional AND, Nursing, being found 440 articles in total, after the criteria were selected 10 articles to compose this review. The nurse is the professional qualified to manage the entire anesthetic-surgical process together with the care process provided to the patient during the perioperative period. Depending on the size of the OR, the nurse may also act as coordinator, performing technical-administrative and managerial functions. Thus, it is expected that this research can serve as a subsidy to guide the political and public guidelines through the functions performed by these professionals in the SC, in order to obtain optimal results for patient safety in the SC.